Lipid Profile Abnormalities in ß-Thalassemia Patients with Multiple Blood Transfusions - Syeda Sabahat Haidar; Mehvish Sana; Rukhsana Tumrani; Farwa Shafqat (Journal of Bahria University Medical and Dental College)
Objective: To determine lipid profile abnormalities in ß -thalassemia patients with multiple blood transfusions in tertiary care hospital.